Malignant Peritoneal Mesothelioma: A Rare Cause of Ascites. (October 2018) - Ibrahim, Abdisamad M.; Al-Akchar, Mohammad; Obaidi, Zainab; Al-Johany, Hamid
Malignant peritoneal mesothelioma (MPM) is a rare diagnosis that presents with difficulties in diagnosis and management. This article reports a case of an 88-year-old male who presented with a 2-week history of abdominal distention and bloating. He worked at an insulation production factory between the ages of 23 and 25 years with presumed asbestos exposure. On the computed tomography scan of the abdomen/pelvis, the patient was found to have diffuse omental, peritoneal, and mesenteric nodularity with moderate to large ascites. Omental biopsy revealed MPM. The overall prognosis of MPM remains poor, with a median survival time of 12 months at the time of diagnosis. Treatment modalities offered in the United States include chemotherapy alone, cytoreductive surgery alone, or cytoreductive surgery/chemotherapy combination.